Should Unemployment Insurance be Centralized in a State Union? - Robert Fenge; Max Friese (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper compares the decentral organization of unemployment insurance in member states of a state union with the central organization at the upper union' level. In a model of two countries the labor force and the firm owners can migrate between the states. Labor markets exhibit unemployment due to trade union's bargaining about the wage rate. In a decentral scenario the states organize independently unemployment insurance and decide about the rate on wages contributed to the insurance budget. Due to open borders they have to take account of migration effects. However, with perfect mobility between the states each government chooses a socially optimal contribution rate such that workers are fully insured against unemployment. In the central scenario the governments overestimate the costs of insurance when bargaining about the contribution rate and observing the common insurance budget of both countries. This leads to a less than socially optimal contribution rate.
Keywords: F66; H77; J65; 330; unemployment insurance policy; state union; centralization; migration externalities